The Role Green Human Resource Management Practices on Environmental Performance: The Mediating Role of Perceived Organisational Support toward the Environment - Delphinus, Letra; Mwita, Kelvin M (SEISENSE (PRIVATE) LIMITED, 2024)
Purpose- This study aimed at examining the role of green human resource management practices on environmental performance. Four green HR practices were involved. These practices include green recruitment and selection, green training and development, green performance management and green compensation management. It further aimed at examining the mediating effect of perceived organisational support toward the environment on the relationship between green HR practices and environmental performance. Design/Methodology- The study used a case study design. Quantitative approach was used through which data was collected using a questionnaire from 198 out of 220 respondents expected which accounts for 90% response rate. Data analysis involved descriptive and inferential statistics. Findings- The study found green recruitment and selection, green training and development, green performance management and green compensation management have significant positive impact on environmental performance. Moreover, perceived organisational support toward the environment was found to have significant effect on the relationship between each green HR practice and environmental performance. The study stresses the need for organisations through their respective management teams to play a supportive role in promoting green HR practices to enhance environmental performance.Practical Implications- Human resource management practices have potential in enhancing environmental performance of organisations. This could be done through integrating green practices with human resource management practices and providing organisational support toward green initiatives.